The Oxford guide to financial modeling : applications for capital markets, corporate finance, risk management, and financial institutions - Ho, Thomas S. Y.; Yi, Sang-bin. (Oxford ; New York : Oxford University Press, 2004)
The book provides a business model framework for determining the optimal corporate strategies necessary to manage a financial institution.
Includes bibliographical references and index.
rua 20/07/16
Loans
Keywords: Finance; Derivative securities; Corporations